‘Meta-societies’ and ‘play communities’. The function of play to Liberian youth football players - Collison, Holly (2013)
This inquiry considers three distinct areas, firstly the Liberian definition of ‘youth’ and their post-conflict identity, secondly the tradition of community and the post conflict living arrangements, and thirdly the theme of this investigation, the use and participation of football and play amongst the ‘youth’ male population; its structure, rules, function, role, frequency, meaning and relationship to the wider society and status.